Analisis Kejadian Hujan Lebat di Wilayah Cilacap Berdasarkan Kondisi Atmosfer, Citra Satelit, dan Indeks Stabilitas (Studi Kasus: Banjir 28 April 2023) - Maghriza, Akhdan Raffi Satya; Haryanto, Yosafat Donny; Munawar, Munawar; Yosafat, Oryza; Silalahi, Nita Florina (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2024)
A heavy rain event that caused flooding hit several areas of Cilacap on April 28, 2022. This flood was triggered by high intensity rain that occurred since Thursday, April 27, 2023. The heavy rain caused the water discharge to overflow and inundate residents' homes. The phenomenon occurred around 17.00-23.30 WIB (10.00-17.30 UTC). This study aims to analyze the causes of extreme rain that occurred in Cilacap. The data used are surface air observation data, rainfall, satellite images, and Radiosonde observation results. The data that has been processed, then analyzed descriptively in terms of temporal and spatial. Surface air analysis conducted from three AWS locations shows conditions that support the occurrence of extreme rain. The highest rainfall measured was 321 mm/day at AWS Digi Cilacap, including the extreme category (>150 mm/day). Himawari-8 Satellite Image Analysis processed with Satellite Animation and Interactive Diagnosis (SATAID) software is used by looking at the temperature of the cloud tops. Based on the results of satellite image analysis, it shows the presence of Cumulonimbus convective clouds with a cloud top temperature value reaching -82.9Ã‚Â°C. Local analysis using Radiosonde at Tunggul Meteorological Station indicates an unstable atmosphere that supports the formation of convective clouds as the cause of heavy rain events in the Cilacap region.